The birth and death of literary theory : regimes of relevance in Russia and beyond - Tihanov, Galin (Stanford University Press, 2019)
A comprehensive account of all major trends in Russian interwar literary theory and its wider impact in our post-deconstruction and world literature era, this book attempts to answer two fundamental questions: What does it mean to think about literature theoretically, and what happens to literary theory when it is no longer available as an option?